Crystallization kinetics for carbon dioxide gas hydrate in fixed bed and stirred tank reactor - Kumar A.; Khatri D.; Lee J.D.; Kumar R. (My University, 2025)
The phase change from germ nuclei to growth nuclei and subsequent volume transformation in a crystallization process was modeled by Avrami equations. The phase change during the hydrate formation was fitted with the classical Avrami model by utilizing gas uptake data. The idea is to understand the difference in growth behavior of hydrate crystals when in small pores compared to a stirred tank reactor which does not pose any physical restrictions to hydrate growth. The parameters n and k of the Avrami equation were determined explicitly for CO2 hydrate formation. © 2016, Korean Institute of Chemical Engineers, Seoul, Korea.